Moving to Testify: Mobilities of Jewish Witnesses in the Trials of War Criminals in People’s Poland (1944-1970) - Kichelewski, Audrey (Sensus Historiae, 2025)
This paper examines Polish Jewish mobilities after 1945 in the context of the trials of those who contributed to the destruction of Polish Jewish communities during the Holocaust. The focus is on trials against Polish citizens, which were still taking place in the 1960s and are less well known in historiography, which has mainly studied the trials of the 1940s, and those against Nazi criminals. Through the study of these trials, cross-referenced with other sources, both Jewish and non-Jewish (correspondence, Memory Books, press, testimonies), we will show that there was considerable circulation within the Polish Jewish world that had survived the Holocaust, extending beyond national borders and the Iron Curtain, and that these survivors sought to be heard at all costs.